Effect of a school-based oral health education in preventing untreated dental caries and increasing knowledge, attitude, and practices among adolescents in Bangladesh. Issue 1 (December 2016) - Haque, Syed; Rahman, Mosiur; Itsuko, Kawashima; Mutahara, Mahmuda; Kayako, Sakisaka; Tsutsumi, Atsuro; Islam, Md.; Mostofa, Md.
Abstract Background There is a dearth of published literature that demonstrates the impact and effectiveness of school-based oral health education (OHE) program in Bangladesh and it is one of the most neglected activities in the field of public health. Keeping this in mind, the objectives of this study were to assess the effectiveness of OHE program in: 1) increasing oral health knowledge, attitude, and practices and 2) decreasing the prevalence of untreated dental caries among 6–8 grade school students in Bangladesh. Methods This intervention study was conducted in Araihazar Thana, Narayanganj district, Bangladesh during April 2012 to March 2013. The total participants were 944 students from three local schools. At baseline, students were assessed for oral health knowledge, attitude and practices using a self-administered structured questionnaire and untreated dental caries was assessed using clinical examination. Follow up study was done after 6 months from baseline. McNemar's chi-square analysis was used to evaluate the impact of OHE program on four recurrent themes of oral health between the baseline and follow-up. Multiple logistic regression analyses were used to determine the impact of the intervention group on our outcome variables. Results Significant improvement was observed regarding school aged adolescents' self-reported higher knowledge, attitude and practices scores (p  < 0.001) at follow-up compared with baseline. The prevalence of untreated dental caries of the study population after the OHE program was significantly (p  < 0.01) reduced to 42.5 %. Multiple logistic regression analyses showed that the OHE intervention remained a significant predictor in reducing the risk of untreated dental caries (adjusted odds ratio [AOR] =0.51; 95 % confidence interval [CI] = 0.37, 0.81). In the follow-up period participants were 2.21 times (95 % CI = 1.87, 3.45) more likely to have higher level of knowledge regarding oral health compared to baseline. Compared with baseline participants in the follow-up were 1.89 times (95 % CI = 1.44–2.87) more likely to have higher attitude towards oral health. In addition, OHE intervention was found to be significantly associated with higher level of practices toward oral health (AOR = 1.64; 95 % CI = 1.12, 3.38). Conclusions This study indicated that OHE intervention was effective in increasing i) knowledge, ii) attitude, and iii) practices towards oral health; it also significantly reduced the prevalence of untreated dental caries among school aged adolescents from grade 6–8 in a deprived rural area of Bangladesh.